`Now lower your butts, Flangheads, and haul away, haul away!'. - Drumm, Russell (Smithsonian)
Describes US Coast Guard Academy cadets' cruise aboard the wind-driven cutter ship `Eagle' as part of their training. Origins of the ship; Journey of the ship; Officer and crew profiles.